View of orchards and golf course in Santa Clara Valley - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Panoramic view of orchards, houses, and a golf course, probably the San Jose Country Club, in Santa Clara Valley, from an unidentified vantage point. There is a broad and varied distribution of orchards along the hills and valley floor. In the center right of the image, a road (possibly Alum Rock Avenue, which turns into Santa Clara Avenue) running east to west can be seen heading towards the other side of the valley, towards the large buildings of downtown San Jose, which are barely visible on the horizon in the distance.